Women Role in Sustainable Supply Chain Strategy in Small and Medium-Sized Enterprises of Small Cities - Iqbal Miftakhul Mujtahid; Titi Darmi (International Journal of Supply Chain Management, 2020)
Abstract. There are many opportunities for companies to promote gender equality in supply chains—through their own actions, by enabling business partners, and by influencing industry peers and the broader policy landscape. Taking any of these steps will help drive progress for women in supply chains. However, we believe that those companies looking to create real and lasting change for women should adopt holistic approaches that tackle inequality at every level. The methods used were qualitative and quantitative descriptive. A master data source was obtained from a key informant of the Sidoluhur Head, Secretary, 2 Hamlet Heads, and 1 Public Figure. The other master data was conducted by administering questionnaires to respondents and determining respondents using accidental sampling. Secondary data obtained from varieties of literature, previous research results, Laws, Government Regulations, and Village Performance Reports as well as other records (text files) associated with the research subject. Quantitative research results (presentation, distribution) examined by utilizing an interactive model through data aggregation, data compression, data display, and decision making or data verification. The effects indicated that the woman professionalism of the Sidoluhur Village Head was categorized Good, the Village Head already had 1) basic ability to cognize about the regulation and the primary tasks and functions (Tupoksi); 2) management capability in handling human resources, finance, village assets, and public service management; 3) technical capability to manage village administration, make village regulations, development planning and budgeting (APBDes) and be able to help the residential district. Results demonstrated that the women roles can be effective in the supply chain process for the SMEs as the management and effective chain roles.